2005
DOI: 10.1021/ie0500366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ti3+ Present in Titania on Characteristics and Catalytic Properties of the Co/TiO2 Catalyst

Abstract: This work investigated the effect of the defect structure referred to as Ti3+ present in titania support of supported titania on characteristics and activity of the Co/TiO2 catalyst. Titania supports were prepared by sol−gel and then calcined under N2 plus increasing the amount of O2 to change the surface defect concentration. The surface defect of titania support was increased by increasing the oxygen percent in feed during the calcination process. This defect was monitored using the CO2-temperature program r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 23 publications
7
53
0
Order By: Relevance
“…In previous studies, various metal dopants, including cobalt (Co) [38,39], barium (Ba) [40], manganese (Mn) [41], nickel (Ni) [42], copper (Cu) [43], zinc (Zn) [44], and iron (Fe) [45,46], have been analyzed for their abilities to enhance the photocatalytic performance of nano-doped-TiO 2 . They improve nano-dopedTiO 2 performance under visible light irradiation by shifting the absorption spectra to a lower energy region [47].…”
Section: Effect Of Metal Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, various metal dopants, including cobalt (Co) [38,39], barium (Ba) [40], manganese (Mn) [41], nickel (Ni) [42], copper (Cu) [43], zinc (Zn) [44], and iron (Fe) [45,46], have been analyzed for their abilities to enhance the photocatalytic performance of nano-doped-TiO 2 . They improve nano-dopedTiO 2 performance under visible light irradiation by shifting the absorption spectra to a lower energy region [47].…”
Section: Effect Of Metal Dopingmentioning
confidence: 99%
“…Suriye et al [39] found that codoped TiO 2 exhibited high anatase phase based on X-ray diffraction (XRD) patterns. Smaller particle size of Ba-doped TiO 2 were synthesized by Atashfaraz et al [40] who reacted titanium dioxide and barium hydroxide at high temperature in the flow reactor.…”
Section: Effect Of Metal Dopingmentioning
confidence: 99%
“…For examples, rutile TiO 2 prepared under Ar and H 2 atmosphere showed higher photocatalytic activity than that prepared under air atmosphere [13]. Suriye et al [14] reported that the surface Ti 3+ varied with the amount of oxygen fed during calcination.…”
Section: Introductionmentioning
confidence: 99%
“…The use of TiPOT for the preparation of Ti-Si composites apparently resulted in an increasing of the reducibility of cobalt [8] and nickel oxide [26]. Furthermore, previous reports suggested that the presence of Ti 3+ in titania can enhance the reducibility [27]. One possible reason for the increased reducibility of NiTiSSP and NiTiMCM can be explained upon the absence of nickel silicate compound as mentioned earlier.…”
Section: Fig 2 Xrd Patterns Of Different Supports (Left) and Differmentioning
confidence: 82%
“…The binding energy at 94.7 eV was assigned to the occurrence of silicate (SixOy except SiO2) on the catalysts surface [8,21]. The formation of surface silicates during preliminary steps of catalyst preparation was considered as a probably reason for partial reduction of the total nickel present at the temperatures normally used up to 500 o C. However, the addition of titania onto the silica or silicon dioxide support of NiTiSSP and NiTiMCM apparently resulting in the absence of binding energy for surface silicate compound [27]. TPR measurements were executed to study the reduction behaviors of all nickel catalysts.…”
Section: Fig 2 Xrd Patterns Of Different Supports (Left) and Differmentioning
confidence: 99%